I want you to panic: a discourse analysis on the ways memes express affective responses when shared to protest climate change - Sakas, Michael Elizabeth, author; Humphrey, Michael, advisor; Badia, Lynn, committee member; Champ, Joseph, committee member (Colorado State University. Libraries, 2023)
This study analyzes how memes express affect when used to protest inaction on climate change. The climate movement is youth-led and young people use Instagram to create and share climate memes. These memes are hashtagged with #ClimateStrike and other similar words that then add these memes to the climate protest conversation. This study on how climate memes express affective responses increases our understanding of what is driving students to join this youth climate strike movement. This study conducted a critical discourse analysis to identify what important themes emerged when protestors used climate change memes to communicate affective responses. In total 400 memes were collected for this research. Half of them are graphic-based climate memes and the other half are protest-based climate memes. The content of these memes were then analyzed to find what affective responses were most often present. Negative emotions dominated the affective sentiment of both the graphic-based climate memes and the protest-based climate memes. The majority of the 400 memes shared negative emotions associated with feelings like frustration, criticism, fear and helplessness. Positive affective responses were associated with climate solutions, individual action and joining the youth climate movement. When memes share feelings of suffering, fear and despair, those memes call out groups in power who are doing little to halt climate change. If these protestors feel that nothing is being done to save the planet and their future, these negative emotions could be playing a role in their motivation to join the youth climate movement.
Keywords: Fridays for Future; Instagram; youth climate strike movement; Thunberg, Greta; climate change; memes